Daily Outpatient Physical Therapy for a Toddler With a Neurodegenerative Disease: A Case Report. Issue 2 (15th April 2022) - Bican, Rachel; Ferrante, Rachel; Hendershot, Sarah; Byars, Michelle; Lo, Warren; Heathcock, Jill C.
Abstract : Purpose: This case report highlights the potential value of delivering a high-dose physical therapy (PT) intervention for a child with a neurodegenerative disease. We include developmental outcomes for a 23-month-old toddler with biallelic TBCD gene mutations following daily outpatient PT. Summary of Key Points: The child had clinical improvements in gross and fine motor, cognition, expressive and receptive language, socioemotional, and adaptive behavior function as determined through Goal Attainment Scaling, Gross Motor Function Measure, and Bayley Scales of Infant and Toddler Development following daily PT intervention. Statement of Conclusion and Recommendations for Clinical Practice: High-dose outpatient PT may be beneficial for a child with a neurodegenerative disease at some time frames. In selected cases, if the neurodegenerative disease slowly progresses, high-dose PT may be a treatment option to promote motor change.